2010
DOI: 10.1136/bcr.03.2010.2805
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intracerebral haemorrhages; which came first, the supra-tentoral or the infra-tentorial one?

Abstract: SummaryThe occurrence of simultaneous spontaneous non-traumatic hypertensive intracerebral haemorrhages (ICHs) is a rare event that carries a considerable morbidity and mortality. These haematomas constitute 0.7-2% of all hypertensive ICHs. We report a 42-year-old man with ischaemic heart disease who presented with sudden severe pancephalic headache, repeated vomiting and left-sided weakness. His work-up revealed two right-sided ICHs: putamenal and cerebellar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…[23] As for the hemorrhagic stroke, it has been suggested that the presence of LVH is a mere marker of chronic hypertension and wide-spread end-organ damage, including intracerebral Charcot-Bouchard microaneurysm formation and rupture. [16,24,25] According to Di Tullio and colleagues, [26] LVH appeared to be independently associated with stroke, regardless of the age, sex, and ethnicity of the target population, and this is consistent with our observations. However, the increased prevalence among our Kurdish hemorrhagic stroke patients needs further analysis.…”
Section: Discussionsupporting
confidence: 92%
“…[23] As for the hemorrhagic stroke, it has been suggested that the presence of LVH is a mere marker of chronic hypertension and wide-spread end-organ damage, including intracerebral Charcot-Bouchard microaneurysm formation and rupture. [16,24,25] According to Di Tullio and colleagues, [26] LVH appeared to be independently associated with stroke, regardless of the age, sex, and ethnicity of the target population, and this is consistent with our observations. However, the increased prevalence among our Kurdish hemorrhagic stroke patients needs further analysis.…”
Section: Discussionsupporting
confidence: 92%
“…However, Stemer et al 13 reviewed 522 consecutive patients admitted to their institution with hypertensive ICH between August 2006 and November 2009 and found that 5.6% of their patients had multiple/simultaneous hypertensive ICHs. In our previous report,4 the highest reported incidence was around 2%; therefore, Maurino et al 's12 work delivers a message that simultaneous ICHs might have been more common that reported.…”
Section: Discussionmentioning
confidence: 81%
“…Apart from Kohshi et al 's paper,14 the available literature does not credit this site as one of the usual combination targets; therefore, it seems that this localisation is a rare one. Previously, we reported on the same subject but that patient had ipsilateral right-sided putamenal and cerebellar haemorrhages 4. The pertinent medical literature8–14 does not mention whether the left side of the brain is more commonly involved than the right one.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Multiple simultaneous intracerebral haemorrhages occur more commonly in a second form [1], and primary multiple simultaneous intracerebral haemorrhages have a much lower incidence varying from 0.75 to 3.0% of all cases of spontaneous intracerebral hemorrhage [1,4]. As for the possible mechanism behind the development of simultaneous/multiple hypertensive hemorrhages, some authors suggested that the bleeding might have occurred simultaneously in different regions of the brain, or that the initial bleeding was followed after a short time by a secondary one at another site due to high intracranial pressure and circulatory disturbance [4,5].…”
Section: Introductionmentioning
confidence: 99%